2000
DOI: 10.1097/00000374-200002000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Deficits in Sober Alcoholics: Influences of Chronicity and Recent Alcohol Consumption

Abstract: These data provide weak support for a dose effect relationship between degree of NP impairment and level of alcoholic drinking in the past 6 months but no evidence for an influence of chronicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
1
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 16 publications
5
39
1
1
Order By: Relevance
“…Some studies have suggested that cognitive performance worsens in direct proportion to the severity and duration of alcoholism (Beatty et al, 2000;Parsons and Nixon, 1998). However, as in other studies, we detected no relationship between neuropsychological performance and drinking history or alcohol-related biological variables (Noel et al, 2001b;Schafer et al, 1991).…”
Section: Discussionsupporting
confidence: 49%
“…Some studies have suggested that cognitive performance worsens in direct proportion to the severity and duration of alcoholism (Beatty et al, 2000;Parsons and Nixon, 1998). However, as in other studies, we detected no relationship between neuropsychological performance and drinking history or alcohol-related biological variables (Noel et al, 2001b;Schafer et al, 1991).…”
Section: Discussionsupporting
confidence: 49%
“…It is associated with more severe cocaine dependence (Higgins et al, 1994) and higher reports of adverse cocaine use consequences (Heil et al, 2001). NP deficits, such as attention, memory, and executive and motor functions, are commonly impaired with chronic alcohol use (Parsons and Nixon, 1993;Beatty et al, 2000;Ikeda et al, 2003); however, it is unclear how alcohol is related to NP deficits in cocaine addiction. Therefore, the current study examined whether cigarette smoking and alcohol use are differentially associated with NP performance in CUD.…”
Section: Nicotine and Alcohol Usementioning
confidence: 99%
“…Studies attempting to link neuropsychological test performance with clinically relevant outcomes in this population have also been largely unsuccessful (Jin et al, 1998;Macciocchi et al, 1989). Executive dysfunction, in particular, is likely to be the result of complex processes, because significant associations with indices of drinking chronicity are rarely found [see Adams and Grant (1986) or Beatty et al (2000) for discussions of these factors]. The development of models that propose more complex mediated relationships between consumption history and cognitive functioning is merited.…”
Section: Self-perception Of Cognitive Deficitsmentioning
confidence: 99%